Pedagogy Evaluations by Indonesian Teachers Implementing Quality Teaching Rounds: An Initial Exploratory Qualitative Study - Walker, Hannah-Charis O. O.; Niswanto, Niswanto; Usman, Nasir; Harnita, Fahlida (Jurnal Pendidikan Progresif, 2024)
Pedagogy Evaluations by Indonesian Teachers Implementing Quality Teaching Rounds: An Initial Exploratory Qualitative Study. Objectives: QTR research in Indonesia has been limited to experimental research on selected aspects of the program. This preliminary study in a qualitative explanatory sequence aimed to describe Indonesian teachers’ individual pedagogy evaluations during a high-fidelity application of the Quality Teaching Rounds (QTR) program, using comparisons with expert evaluations.  A deductive, “top-down” approach to theme-finding provided hard data in this under-researched area, to be further investigated in later studies. Methods: Eight teachers from two schools were recruited to implement QTR. In school-based professional learning communities, teachers observed lessons, used the Quality Teaching Model to assign kodes (evaluations) to pedagogy using ‘Koding Sheets’, then discussed their kodes. Koding Sheets were collected as primary data, and teacher initial kodes verified using discussion transcripts. Expert evaluations were created by an Australian internal expert using Quality Teaching Model rubrics, observation notes and consultations with Indonesian educators and an external expert. Koding Sheets were collated and colour-coded as ‘the same’, ‘higher’, or ‘lower’ than expert kodes. Frequencies were tabulated using Excel to find overarching themes or patterns addressing the research question. Findings: Themes included: (1) Dissimilarity of teacher kodes to expert kodes; (2) Prevalence of overestimating in kodes; (3) Trends of ‘same’ kodes increased for many and decreased for some; and (4) professional learning community-based differences in trends and counts. Results suggest social constructionism explains teacher learning leading to evaluation patterns, as well as the presence and influence of language, cultural, school contextual, relational factors on teacher pedagogy evaluations. Conclusion: Recommended research is outlined to confirm, identify, measure and determine how to mitigate these factors, to enable recommendations as to the suitability of QTR with the Indonesian context. Keywords: evaluation, indonesian teachers, pedagogy evaluation, qualitative exploratory method, quality teaching rounds.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024101